Safety is the indicator of physiological traits aviation specialists as a socio-psychological aspect - Орленко, Н.А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2012)
Influence of human factors on safety in the process of training future pilots in high school vocational and applied by means of physical training as one of the most important components in ensuring the development and improvement of physical and psychophysical properties with regard to the characteristics of future employment, allowing prospective pilots successfully learn, and Aviation industry experts - to work effectively.